Fire tablets for dummies - Muir, Nancy 1954- (John Wiley & Sons, 2015)
If you're the proud owner of a Fire tablet, this guide helps you make the most of its capabilities. Muir will be with you as you take the Fire tablet out of the box, find out how to use the touchscreen and settings, buy and play music and movies, and get connected with social networking sites and your email account.
Print version record
Keywords: Kindle Fire (Computer); Tablet computers; Kindle Fire (Ordinateur); Tablettes électroniques